Genesis and interaction of magmas at Nishinoshima volcano in the Ogasawara arc, western Pacific: new insights from submarine deposits of the 2020 explosive eruptions - Tamura, Yoshihiko; Sato, Tomoki; Ishizuka, Osamu; McIntosh, Iona M.; Yoshida, Kenta; Maeno, Fukashi; Chang, Qing (Frontiers in Earth Science, 2023)
Sudden changes of eruption styles and magma compositions at arc volcanoes are enigmatic processes. Nishinoshima volcano, western Pacific, has had historical eruptions in 1973–1974 and from 2013 on and off to the present day. These eruptions were characterized by effusive Strombolian eruptions of andesite magmas until mid-June 2020, when they suddenly transitioned to violent explosive Strombolian eruptions that produced tephra fallout over a wide area. To understand this transition, we conducted marine surveys and sampling of the extensive submarine deposits of the tephra fallout. Our new data demonstrate that the full compositional range of the 2020 eruptions spans from basalt to dacite. We present evidence for magma mixing of newly injected basalt with andesite magmas. Nishinoshima consists of an andesitic main edifice surrounded by basaltic knolls: previous studies have shown that Nishinoshima andesite compositions can be generated by olivine fractionation of primary andesitic magmas that result from partial melting of hydrous mantle at relatively low pressures under the thin crust of the Ogasawara arc; knoll basalt compositions can be generated by partial melting of mantle at greater depths and were interpreted as older events of the volcano. We show that basalt magmas could have been generated throughout the entire history of Nishinoshima. In addition, we show that andesites from Nishinoshima and nearby Nishinoshima-Minami Knoll, which are only ∼8 km apart, have distinct subduction components. Together, these data improve our understanding of the diverse primary magmas responsible for the construction and continuing eruptive activity of an active island arc volcano.